IL-17 plasma levels and erythrocyte sedimentation rate on oral candidiasis animal model - Erna Sulistyani; Iin Eliana Triwahyuni; Happy Harmono; Lisa Miftakhul Janna; Saikha Adila Azzah; Muchamad Ziyad Afif; Ainunnusak Ayuningtyas (Dental Journal, 2022)
Background: A study with female animal models is important because the system immune of females is remarkably different from the male because of interaction between sex hormone and immune system. Interleukin-17 (IL-17) plays an important role in immune response toward Candida albicans (C. albicans) infection and Erythrocyte Sedimentation Rate (ERS) is an easy and sensitive test to assess the inflammation. Purpose: This study aimed to evaluate C. albicans infection, analyse the IL-17 levels and ESR in a female animal model of oral candidiasis. Methods: Female Wistar rats were used as oral candidiasis animal model. The rats divided into three groups (pre-treatment group (P0), 5th-day post-treatment group (P1) and 8th-day post- treatment group (P1). Each group consists of six rats. After the adaptation period, the P0 was sacrificed. The drinking water of the P1 and P2 was added tetracycline HCl 500mg /1L. On the day before and after inoculation C. albicans, Methylprednisolone was injected. Ten minutes before inoculation with 0.3 ml C. albicans 9.4 x 107/mL, rats were sedated by CPZ 0.7 mg IM. The rats in P1 group were sacrificed after five days and in P2 were sacrificed eight days after inoculation. The IL-17 plasma levels measured by enzyme-linked immunosorbent assay (ELISA), decreased on the 5th day but not on the 8th-day post-treatment. The obtained data were analyzed by parametric and non-parametric tests according to normality and homogeneity of the data with p<0.05. Results: The colony forming unit (CFU) of C. albicans collected over the mouth on increased almost 8-fold and on 8th-day post-treatment almost 3-fold compared with pre-treatment. The ESR increased on the 8th day but not on the 5th-day post-treatment. Conclusion: The IL-17 level was decreased on the 3rd day, ESR increased on eight days after inoculation of C. albicans in female rats’ model of oral candidiasis.